Analysis of Employee Performance Planning in the Ministry of Religious Affairs of Karawang Regency - Mesti Rosalia; Uus Mohammad Darul Fadli; Laras Ratu Khalida (Research in Management of Technology and Business, 2024)
To analyze employee performance planning at the Karawang Regency Ministry of Religious Affairs, based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 6 of 2022. This research contains points to clarify the four components, namely work planning, especially HR inventory, HR Forecasting, HR Planning, and Monitoring and Evaluation which aim to hone employee skills and improve services to the community. The research method applied is a qualitative approach based on data analysis using content analysis. The resource persons in this study consisted of the Head of the Ministry of Religious Affairs (K1), Head of the Personnel Section (K2), Employee (P1), Employee (P2), Employee (P3). Primary data is obtained during coordinative interviews with respondents, while secondary data is obtained from literature study and documentation.